Does the “Tian-Ren-He-Yi” Belief System Promote Corporate Environmental Performance? - Lai, Jieji; Liu, Bin; Wang, Hong (Frontiers in Psychology, 2022)
Buddhism and Taoism are among two of the major religions in China. Their “Tian-ren-he-yi” belief system promotes a conception of harmony between man and nature, which is an important guide for the construction of ecological civilization in China. Using data from Chinese listed manufacturing companies, this paper explores the impact and mechanism of Chinese local religious beliefs on corporate environmental governance. The results indicate that this belief system can improve corporate environmental performance. Furthermore, mechanism tests show that the “Tian-ren-he-yi” belief system promotes corporate environmental practices by reducing the pressure on management to achieve economic performance goals and increasing investment in environmental protection. Finally, the impact of the belief system on corporate environmental performance is more efficacious when the enterprises are under weak external supervision. Our results imply that the traditional religious culture is an important factor that influences corporate environmental performance in Chinese business practices.